PENINGKATAN HASIL BELAJAR IPAS MELALUI PENDEKATAN DEEP LEARNING BERBANTUAN WORDWALL DI KELAS IV SDN 05 AIR TAWAR BARAT KOTA PADANG - Kurnia Rahmadhani, Niela; Amsari, Dina; Putri Zulkarnaini, Aissy; Fitria, Yanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low academic achievement of students I IPAS instruction. This is due to teaching that remains teacher centred, suboptimal instructional modules, a lack of problem solving and group discussion, a failure to connect the material to everyday life, and minimal use of instructional media. These conditions result in student being less active, less motivated, and easily bored during the learning process. Therefore, learning, innovations are needed to enhance student engagement and learning outcomes. This study aims to improve student learning oucomes through the application of a Wordwall assisted Deep Learning approach in fourth grade classrooms. The research design employed wa Clasroom Action Research (CAR) using both qualitative and quantitative approaches. The study was conducted in two cycles, each comprising the planning, implementation, observation, and reflection stages. Data were collected through both test and non test techniques. The research subjects consisted of a fourth grade theacher serving as an observer, the researcher as the practitioner, and 27 fourth grade stundents at SDN 05 Air Tawat Barat in Padang City. The research results indicate improvements in every aspect. The teaching module score increased from an average of 80,28 (C) in Cycle I to 95,23 (SB) in Cyle II. Theacer activity increased from 85,30 (B) to 95,23 (SB). Student activity increased from 80,49 (C) to 95,23 (SB). Students learning outcomes improved from 71,41 (C) in Cycle I to 85,18 (B) in Cyle II. Thus, it can be concluded that the implementation of the Wordwall assisted Deep Learning approach effectively improves student learning outcames.